Perlindungan Konsumen Terhadap Keamanan Pangan Jajanan (Street Food) Sebagai Bentuk Tanggung Jawab Negara - Anna S. Wahongan; Kathleen C. Pontoh; Grace Karwur; Steven S. Gugu; Firman Mustika (Bulletin of Community Engagement, 2026)
This study aims to examine consumer protection in terms of state responsibility and to analyze the supervision of food safety for street-vended food in Indonesia. This study employs a qualitative method using a descriptive analytical approach and doctrinal legal research, incorporating statutory and conceptual approaches. The study utilizes primary legal materials that are authoritative and binding, including laws and regulations, as well as secondary legal materials. The data are analyzed using legal interpretation techniques. The findings indicate that the government should strengthen its supervision of the safety of street-vended food as part of its responsibility to protect consumers. Such supervision should cover the entire food chain, beginning with the selection and quality of food ingredients, followed by the preparation and processing stages, and extending to food presentation. In addition, the government should provide guidance and education to food vendors and impose appropriate legal sanctions when their products endanger the health and safety of consumers. Strengthening comprehensive and continuous supervision is therefore essential to ensure food safety and provide effective consumer protection for street-vended food in Indonesia. This study contributes to the development of consumer protection law by providing a comprehensive legal framework for understanding the state's responsibility in ensuring the safety of street-vended food. It also highlights the importance of integrated government supervision, preventive measures, and effective law enforcement to strengthen consumer protection and ensure the fulfillment of consumers' rights to safe and healthy food in Indonesia.